2012
DOI: 10.1007/s00784-012-0790-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical longevity of ceramic laminate veneers bonded to teeth with and without existing composite restorations up to 40 months

Abstract: OBJECTIVES: This study evaluated the survival rate of ceramic laminate veneers bonded to teeth with and without existing composite restorations (ECR). MATERIALS AND METHODS: Twenty patients (mean age: 49.7 years) received 92 feldspathic ceramic laminate veneers (Shofu Vintage AL) on the maxillary teeth (intact teeth: n = 26; teeth with ECR: n = 66). Preparations with incisal overlap were made, and ECR of good quality were not removed but conditioned using silica coating (CoJet) and silanization (ESPE-Sil). Ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
3
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 21 publications
1
50
3
12
Order By: Relevance
“…However, in an in vitro study, ceramic laminate veneers bonded to a complete composite surface presented higher fracture strength results than those bonded onto enamel [20]. Similarly, clinical survival rate of laminate veneers bonded onto teeth with existing composite restorations after the latter was tribochemical silicacoated, was not less than those bonded on enamel/dentin up to 40 months of evaluation [21]. Thus, it can be anticipated that the presence of adhesive resin would also not impair the bond strength of laminate veneers on the IDS.…”
Section: Introductionmentioning
confidence: 99%
“…However, in an in vitro study, ceramic laminate veneers bonded to a complete composite surface presented higher fracture strength results than those bonded onto enamel [20]. Similarly, clinical survival rate of laminate veneers bonded onto teeth with existing composite restorations after the latter was tribochemical silicacoated, was not less than those bonded on enamel/dentin up to 40 months of evaluation [21]. Thus, it can be anticipated that the presence of adhesive resin would also not impair the bond strength of laminate veneers on the IDS.…”
Section: Introductionmentioning
confidence: 99%
“…The small amount of preparation that allows teeth wear limited to enamel makes the technique appropriate once the dentistry increasingly recommends conservative procedures. According to the data found in the literature by the authors, the mean of clinical follow-up nearest to this clinical report evaluation period was 21.6 months (GRESNIGT; KALK; OZCAN, 2013). In this period, the feldspathic ceramic veneers obtained survival rate of 94.6%.…”
Section: Discussionmentioning
confidence: 59%
“…The improvements of dental materials have made ceramic a desirable option for indirect aesthetic restorative procedures (GRESNIGT; KALK; OZCAN, 2013;MORIMOTO et al, 2016). The cumulative survive rate is 87% with a medium followed-up of 8 years for feldsptathic ceramics (MORIMOTO et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the scientific literature is more extensive for ceramic laminates, a recently published clinical trial (with a 3-years follow-up) has reported no significant difference in the survival rate of composite (87%) and ceramic (100%) veneers; on the other hand, some surface quality changes were more frequently observed for the resin materials (i.e., minor voids and defects and slight staining at the margins) [26]. In addition, the survival rate and clinical performance of composite or ceramic laminate veneers were not significantly influenced when bonded onto intact elements or onto teeth with preexisting composite restorations (when no caries or infiltration is present, of course) [27, 28]. As a final recommendation, like after the delivering of many other types of indirect restorations, the dentist should plan a careful follow-up program and give patients appropriate instructions for maintenance and preservation of the obtained success.…”
Section: Discussionmentioning
confidence: 99%